Propose of models to estimate toughness as a function of physical and chemical properties of commercial thermally modified hardwoods - Oliveira, Carolina Aparecida Barros [UNESP]; de Oliveira, Karina Aparecida [UNESP]; Aquino, Vinicius Borges de Moura; Christoforo, André Luis; Molina, Julio Cesar [UNESP] (FapUNIFESP (SciELO), 2022)
The present research intended to propose and evaluate regression models which estimate toughness property as a function of physical, chemical properties of thermally modified hardwood and thermal treatment temperature, using linear, quad-ratic, cubic, exponential, logarithmic, geometric and multiple linear models. Commercial thermally modified woods were used on the study, being characterized for all referred properties, totalizing 450 experimental determinations. The ana-lyzed models presented a low and moderate coefficient of determination, indicating the impossibility to use such models in the estimation of toughness as a function of physical and chemical factors.
Keywords: Chemical properties; Hardwoods; Physical properties; Regression models; Thermal modified wood